In-house wireless optical communication; Unguided optical communication for ethernet connection; Design of zero dispersion optical fiber (part 2); Hearing integrity of the fifth year communication student vs socio-background; Sensing with ultrasonic sensor; Modelling of fiber optic transmission system by using Matlab / [mikrofilem] - Chong, Yu Seng; Hasbullah Abdullah; Mohd. Sayuti Shamsuri; Rafidah Abdul Ghani; Thevindran, Thevaraj; Tuan Zainal Abidin Tuan Besar (Sekudai : Universiti Teknologi Malaysia, 1996)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1996